Circulating microRNAs and endothelial cell migration rate are associated with metabolic syndrome and fitness level in postmenopausal African American women. Issue 14 (25th July 2019) - Sapp, Ryan M.; Shill, Daniel D.; Dash, Chiranjeev; Hicks, Jennifer C.; Adams‐Campbell, Lucile L.; Hagberg, James M.
Abstract: Postmenopausal African American women are at elevated risk for metabolic syndrome (MetS), which predisposes them to cardiovascular disease and other chronic diseases. Circulating microRNAs (ci‐miR) are potential mediators of cardiometabolic diseases also impacted by cardiorespiratory fitness (CRF) level. Using real‐time quantitative PCR, we compared the expression of vascular‐related ci‐miRs (miR‐21‐5p, miR‐92a‐3p, miR‐126‐5p, miR‐146a‐5p, miR‐150‐5p, miR‐221‐3p) in sedentary, overweight/obese, postmenopausal African American women based on 1) presence ( n = 31) or absence ( n = 42) of MetS and 2) CRF level (VO2peak ) (Very Low < 18.0 mL·kg −1 ·min −1 [ n = 31], Low = 18.0–22.0 mL·kg −1 ·min −1 [ n = 24], or Moderate >22.0 mL·kg −1 ·min −1 [ n = 18]). Endothelial migration rate in response to subjects' serum was assessed to determine the effect of circulating blood‐borne factors on endothelial repair. Ci‐miR‐21‐5p was the only ci‐miR that differed between women with MetS compared to those without MetS (0.93 ± 0.43 vs. 1.28 ± 0.71, P = 0.03). There were borderline significant differences ( P = 0.06–0.09) in ci‐miR‐21‐5p, 126‐5p, and 221‐3p levels between the CRF groups, and these three ci‐miRs correlated with VO2peak ( r = −0.25 to −0.28, P < 0.05). Endothelial migration rate was impaired in response to serum from women with MetS compared to those without after 16–24 h. Serum from women with Moderate CRF induced greater endothelial migration than the Very Low and Low CRF groups after 4 and 16–24 h, that was also not different from a young, healthy reference group. Ci‐miR‐21‐5p is lower in postmenopausal African American women with MetS, while ci‐miRs‐21‐5p, 126‐5p, and 221‐3p are associated with CRF. Factors which impair endothelial cell migration rate are present in serum of women with MetS, though having Moderate CRF may be protective. Abstract : We found that in postmenopausal, African American women, circulating blood‐borne factors are altered in association with metabolic syndrome and cardiorespiratory fitness, such that endothelial migration rate is impaired in response to serum from women with metabolic syndrome and with a lower fitness level. The level of circulating microRNA 21‐5p in serum was lower in women with metabolic syndrome compared to those without, while other circulating microRNAs related to endothelial function correlated with cardiorespiratory fitness. Thus, in this high risk group for cardiovascular disease, maintaining a healthy metabolic profile and at least a moderate fitness level may be protective for cardiovascular health through maintenance of circulating factors that promote endothelial repair.